Environmental impacts of heavy metals, rare earth elements and natural radionuclides in marine sediment from Ras Tanura, Saudi Arabia along the Arabian Gulf. (February 2018) - El-Taher, Atef; Alshahri, Fatimh; Elsaman, Reda
Abstract: Ras Tanura city is one of the most important cities in Saudi Arabia because of the presence of the largest and oldest oil refinery in the Middle East which was began operations in September 1945. Also its contains gas plant and two ports. The concentration of natural radionuclides, heavy metals and rare earth elements were measured in marine sediment samples collected from Ras Tanura. The specific activities of 238 U, 226 Ra, 232 Th, 40 K and 137 Cs (Bq/kg) were measured using A hyper-pure Germanium detector (HPGe), and ranged from (20.4 ± 4.0–55.1 ± 9.9), (6.71 ± 0.7–46.1 ± 4.5), (3.51 ± 0.5–18.2 ± 1.5), (105 ± 4.4–492 ± 13) and from (0.33 ± 0.04–2.10 ± 0.4) for 238 U, 226 Ra, 232 Th, 40 K and 137 Cs respectively. Heavy metals and rare earth elements were measured using ICPE-9820 Plasma Atomic Emission Spectrometer. Also the frequency distributions for all radioactive variables in sediment samples were analyzed. Finally the radiological hazards due to natural radionuclides in marine sediment were calculated to the public and it's diagramed by Surfer program in maps. Comparing with the international recommended values, its values found to be within the international level. Highlights: Ras Tanura city is one of the most important cities in Saudi Arabia. The concentration of natural radionuclides, heavy metals and rare earth elements were measured. The specific activities of 238U, 226Ra, 232Th, 40 K and 137Cs (Bq/kg) were measured. Heavy metals and rare earth elements were measured using ICPE-9820 Plasma Atomic Emission Spectrometer.